EXPERIMENTAL VERIFICATION OF THE EFFECTIVENESS OF LEARNING ALGORITHMIZATION AND PROGRAMMING IN SECONDARY SCHOOL BASED ON NATIONAL SPECIFICATIONS - Oshanova, Н.Т; Аnuarbekova, Г.Ж (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2020)
This article discusses a pedagogical experiment in teaching algorithmization and programming at school by solving systems of problems based on national characteristics. The pedagogical experiment is conducted in accordance with three stages. At the first ascertaining stage, an analysis of the needs and achievements of learning algorithmization and programming by solving a system of problems based on national characteristics is made. At the second stage of formation, the work on the implementation of the developed methodology for teaching algorithmization and programming by solving a system of problems based on national characteristics is clarified. At the third stage of control, experimental results of the methodology for teaching algorithmization and programming are generalized and processed by solving a system of problems based on national characteristics. Control tasks for the subsection "algorithmization and programming" for students of grade 7 and grade 8 are given. As a result of experimental work, the effectiveness of the developed methodology for teaching programming and algorithmization in school is checked by solving systems of problems based on national characteristics.